Enhancing the Competency of Facilitators and Accelerating Halal Certificate Registration - Makiah, Zulpa; Sauri, Supian; Wicaksono, Ardian Trio; Fatya, Alvian Ikhsanul; Khairunnisa, Khairunnisa; Rahmawati, Helda; Astutik, Trining Puji; Haitami, Iqbal; Hafidzi, Anwar; Nazmi, Nahdia (Universitas Lambung Mangkurat, 2025)
The primary focus of this community service initiative is to improve the abilities of Halal Product Process facilitators (P3H) and to expedite halal certification acquisition for stakeholders in South Kalimantan through the self-declaration scheme. The methods used are mentoring and workshops, which are then carried out by holding a Focus Group Discussion (FGD). The number of P3H who participated in this event was 100 participants. The findings and outcomes of the event can be described through the enhancement of facilitators' competency, which has an impact on increasing the number of halal certificates issued in the South Kalimantan area. In 2022, 893 halal certificates have been issued, followed by 1,588 certificates from January 1st to July 14th, 2023. This number increased significantly to 3,286 certificates issued from July 15th to December 31st, 2023, after the implementation of community service. As a result, this community service has proven effective in accelerating halal certification for MSMEs.